The role of the school administration in improving the educational process in girls secondary schools in Khamis Mushait governorate: field study - Saeed, Safaih Dafer (Journal of Educational and Psychological Sciences, 2019)
The study aimed to identify the role of the school administration in improving the professional growth of female teachers, improving the students’ affairs, improving the curriculum and evaluating the contribution of the school administration to the success of the educational process in secondary schools for girls in Khamis Mushait governorate. The study was based on a descriptive method (analytical). The tool consisted of a questionnaire distributed to a random sample of (156) teachers and administrators of the secondary stage. The study reached many results, the most important of which are: (3.87), ie, (high level of approval) and at the field level; the professional growth of female teachers was at the highest (3.89), followed by female students’ average (3.78), and finally the average (3.47)). The study also found significant differences on the role of the school administration in improving the educational process in the secondary girls’ schools in Khamis Mushait governorate according to the variable of the job, in favor of the departments, while there were no statistically significant differences due to variable years of experience. School administration with educational developments, and developments related to Bedouin As resident supervisors, to raise teachers’ motivation for better performance and to motivate them financially and morally for progress and development.